Digital Marketing Strategy on Agricultural Product (Case Study : UD Amalia Demak) - Amalia, Farah; Widyakto, Ady; Parpti NSS, Lulus (Economics and Business Solutions Journal, 2021)
Offline marketing in agricultural products needs high cost. The high cost of marketing results in a less competitive selling price. Digital marketing is the right solution to this problem. This study aims to analyze the right digital marketing strategy for the company. The analytical method used is the analysis of Sostacs and Aida. The research result states that the company combines offline and online marketing. The media used are the marketplace and social media. The marketplace Agromaret focused on providing complete information regarding massive products and promotions to drive sales transactions. Meanwhile, Social media facebook is focused on building relationships with customers and personal closeness to create customer loyalty.